Fórmulas Básicas de Derivación: Sen Sen
Fórmulas Básicas de Derivación: Sen Sen
Fórmulas Básicas de Derivación: Sen Sen
DEL
CLCULO
d 1 sen tan = (c) = 0 csc = cos dx sen 2 2 sen + cos = 1 1 cos d 2) ( x) =1 sec = cot = dx cos sen tan 2 + 1 = sec 2 1 d 3) ( u v w ...) = d ( u ) d ( v ) d ( w) ... cot = dx dx dx dx tan 1 + cot 2 = csc 2 d 4) sen( + ) = sen cos + cos sen ( cu ) = c d ( u ) dx dx sen( ) = sen cos cos sen d 5) cos( + ) = cos cos sensen ( uv ) = u d ( v ) + v d ( u ) dx dx dx cos( ) = cos cos + sensen tan + tan d tan( + ) = 6) ( uvw) = uv d ( w) + vw d ( u ) + wu d ( v ) 1 tan tan dx dx dx dx tan tan tan( ) = 1 + tan tan d m 7) ( x ) = mx m 1 cos 2 = cos 2 sen 2 dx sen2 = 2 sen cos d m d 1 8) u = mu m 1 (u ) cos 2 = (1 + cos 2 ) dx dx 2 1 sen 2 = (1 cos 2 ) 2 d u 1 d 1 9) ( u ), c 0 sensen = [ cos( ) cos( + )] = dx c c dx 2 1 cos sen cos = [ sen( + ) + sen( )] tan sen 2
1)
( )
1
3 2 4 6
3 2 2 2 2 2 1 3 2 2
0 1 0
3 3
1
1 0 1
d c d 1 c d ( u ), u 0 =c = 2 dx u dx u u dx d d v ( u ) u ( v) d u dx , v0 = dx dx v v2 d ( y ) = d ( y ) d ( w) d ( u ) dx dw du dx
3 2
10)
cos cos =
1 [ cos( + ) + cos( )] 2
11)
12)
13)
14)
15)
16)
17)
18)
19)
20)
21)
22)
d ( senu ) = cos u d ( u ) dx dx d ( cos u ) = senu d ( u ) dx dx d ( tan u ) = sec 2 u d ( u ) dx dx d ( ctgu ) = csc 2 u d ( u ) dx dx d ( sec u ) = sec u tan u d ( u ) dx dx d ( csc u ) = csc u cot u d ( u ) dx dx d 1 ( log a u ) = log a e, a 0, a 1 dx u d 1 d ( ln u ) = (u ) dx u dx d u d ( a ) = a u ln a (u ), a 0 dx dx d u d (e ) = e u dx ( u ) dx
36)
"#.$%."&
37) csc udu = cot u + C [ f (u ) g (u ) ...]du = f (u )du g (u )du ... 25) du = u + C 38) sec u tan udu = sec u + C
2
sec
udu = tan u + C
26)
n u du =
u n +1 + C, n +1
n 1
40)
39)
27)
du = ln u + C u
u
28)
du = e u + C
41)
a u du
= arcsen
29)
a a du = ln a
u
+C
42)
u2 a2 du
u u + C = arccos + C a a 1 u = arcsen + C a a
2
u a
2
= ln u + u 2 a 2 + C
30)
43)
31)
44)
32) 33)
du 1 u a = ln +C 2 a 2a u + a du 1 u + a 45) +C a 2 u 2 = 2a ln u a
du 1 u = arctan + C 2 +a a a
+C
46)
34)
u a2 u a2 u2 + arcsen + C 2 2 a
+C
47)
35)
u a2 u2 a2 ln u + u 2 a 2 + C 2 2
+C
* *udv = uv vdu